Environmental Biotechnology New Approaches and Prospective Applications - Petre, Marian (IntechOpen, 2013)
Taking into consideration the outstanding importance of studying and applying the biological means to remove or mitigate the harmful effects of global pollution on the natural environment, as direct consequences of quantitative expansion and qualitative diversification of persistent and hazardous contaminants, the present book provides useful information regarding New Approaches and Prospective Applications in Environmental Biotechnology. This volume contains twelve chapters divided in the following three parts: biotechnology for conversion of organic wastes, biodegradation of hazardous contaminants and, finally, biotechnological procedures for environmental protection. Each chapter provides detailed information regarding scientific experiments that were carried out in different parts of the world to test different procedures and methods designed to remove or mitigate the impact of hazardous pollutants on environment. The book is addressed to researchers and students with specialties in biotechnology, bioengineering, ecotoxicology, environmental engineering and all those readers who are interested to improve their knowledge in order to keep the Earth healthy.